Pengaruh rasio keuangan terhadap harga saham pada perusahaan sektor kimia di bursa efek Indonesia - Lailynica Sefira; Ahmad Budiman (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This research aims to determine and analyze the effect of financial ratios on stock prices by measuring the financial ratios of Current Ratio, Total Asset Turnover and Debt to Equity Ratio. This research takes the object of chemical sector companies listed on the Indonesia Stock Exchange in the period 2016-2020. The population in this study were 10 companies in the chemical sector, the sampling technique was purposive sampling based on the criteria determined by the researcher. The dependent variable in the study is stock prices, while the independent variables are Current Ratio, Total Asset Turnover and Debt to Equity Ratio. The data analysis method used is multiple linear regression analysis with SPSS version 24 statistical calculator. Based on the t test, the Current Ratio and Total Asset Turnover variables have a significant effect on stock prices, while the Debt to Equity Ratio variable has no significant effect. The results of the feasibility test of the F test model that all variables in the study have a significant effect on stock prices.